2018
DOI: 10.1108/jqme-07-2016-0029
|View full text |Cite
|
Sign up to set email alerts
|

Dependability-based maintenance optimization in healthcare domain

Abstract: Purpose The purpose of this paper is to review maintenance strategies within the healthcare domain and to discuss practical needs as gaps between research and practice. Design/methodology/approach The paper systematically categorizes the published literature on clinical maintenance optimization and then synthesizes it methodically. Findings This study highlights the significant issues relevant to the application of dependability analysis in healthcare maintenance, including the quantitative and qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…Medical Devices Management System is another topic to ensure medical device reliability. Bahreini et al [ 4 , 8 ] distinguished the factors affecting medical equipment maintenance and management and are divided to resources, human resources, financial, physical documentation, education, service, quality control, information bank, inspection and preventive maintenance, training and education, management, services, design, and implementation. Medical Devices Management System in this review highlights marketing strategies [ 34 ], service quality [ 35 , 36 ], replacement plan [ 37 ], utilization and human resource [ 10 ], quality assurance program [ 38 ], and quality control system [ 39 ], where the replacement plan, marketing strategies, and establishment of Standard Operating Procedure (SOP) are essential in management.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical Devices Management System is another topic to ensure medical device reliability. Bahreini et al [ 4 , 8 ] distinguished the factors affecting medical equipment maintenance and management and are divided to resources, human resources, financial, physical documentation, education, service, quality control, information bank, inspection and preventive maintenance, training and education, management, services, design, and implementation. Medical Devices Management System in this review highlights marketing strategies [ 34 ], service quality [ 35 , 36 ], replacement plan [ 37 ], utilization and human resource [ 10 ], quality assurance program [ 38 ], and quality control system [ 39 ], where the replacement plan, marketing strategies, and establishment of Standard Operating Procedure (SOP) are essential in management.…”
Section: Resultsmentioning
confidence: 99%
“…The World Health Organization (WHO) estimates 50–80% of equipment remains nonfunctional due to lack of maintenance culture, lack of competency, and the tendency to emphasis more on corrective maintenance than preventive maintenance [ 3 ]. Deficiency of adequate maintenance of medical devices leads to equipment downtime and reduces device performance, waste cost, and resources [ 4 ]. The data recorded in the Malaysian Government Hospitals database proved that hospital operates with massive number of aging medical devices [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Failures of the medical devices lead to delayed or absent treatment, and effective operational and maintenance management is the main approach to shorten equipment shutdown time and increase healthcare system availability. [135][136][137] Identical equipment used in different circumstances may need different maintenance strategies. Bahreini et al identify seven main influence factors on the effectiveness of maintenances in healthcare, including resources, quality control, information bank, education, service, inspection and preventive maintenance and design and implementation.…”
Section: Risk Reduction In Operation Of Smart Systemsmentioning
confidence: 99%
“…148 More studies about maintenance optimization in the healthcare domain can be found in the review by Mahfoud and co-authors. 135…”
Section: Risk Reduction In Operation Of Smart Systemsmentioning
confidence: 99%
“…The reliability, maintainability, availability, and safety of medical devices are the ultimate goal in maintenance strategy, where medical devices should not fail frequently and must be repaired promptly when the failures are detected. Numerous investigations have associated medical device failures with severe patient injuries and deaths ( Dhillon, 2011 ; Mahfoud, Abdellah & El Biyaali, 2018 ; Palmer, 2010 ; Verbano & Turra, 2010 ). The world health organization (WHO) estimates that 50% to 80% of equipment is non-functional due to the lack of maintenance culture, competency, and a tendency to focus on corrective maintenance rather than preventative maintenance ( Kutor, Agede & Ali, 2017 ).…”
Section: Introductionmentioning
confidence: 99%